UJI AKTIVITAS ANTIRADIKAL BEBAS FRAKSI DIETIL ETER BERUWAS LAUT (Scaevola taccada (Gaertn.) Roxb.) MENGGUNAKAN DPPH - A. Amaliah Dahlia; Rachmat Kosman; Halija Halija (Fakultas Farmasi UMI, 2013)
Radical scavenging activity of diethyl ether fraction from sea lettuce tree (Scaevola taccada (Gaertn.) Roxb.) using DPPH.The of research aims is determine the radical scavenging activity of sea lettuce tree based on the binding of free radical DPPH. Was conducted the research on test radical scavenging activity of sea lettuce tree (Scaevola taccada (Gaertn.) Roxb.) and then compared with the radical scavenging activity Vitamin C. Five thousand grams of sea lettuce tree (Scaevola taccada (Gaertn.) Roxb.) extraced by maceration using ethanol. Dry ethanol extract was partitioned with solid-liquid partition, using diethyl ether and then tested for activity and was obtained radical scavenging IC50 value 27,06 µg/mL.Key Word : Radical Scavenging, Scaevola taccada, DPPH